Interval - Martien Mulder 176 images - Mulder, Martien 1971-; Bakker, Stef; Klein, Carsten 1966- (August Editions, 2022)
The Dutch-born photographer Martien Mulder's (born 1971) new book of images springs from the Japanese concept of ma, which can be described as a pause in time, an interval, or emptiness in space. Teaming up with Amsterdam-based creatives Stef Bakker and Carsten Klein, Mulder embarked on an extensive quest to reveal the ma in his own images, editing from an archive of 25 years of photography. The images in this book are studies of the in-between; some center on details photographed at such close quarters that they lose their context, while others show only the negative space, inactivity or quiet nothingness. The viewing direction of the book is not dictated, nor is the beginning or the end, nor the pace: it can be opened to any page at any time, functioning as an object of contemplation.
Umschlagtitel
Keywords: Mulder, Martien -- 1971-; Fotografie; Bildband